German bakers and their position in the urban economy of Saint-Petersburg in the 19th — early 20th century - Shaidurov V.N.; Osipov V.A. (Вестник археологии, антропологии и этнографии)
The results of the study of the position and role of German bakers within the structure of urban economy of Saint-Petersburg in the 19th — early 20th century have been summarized. The theoretical basis of the research is the theory of frontier modernization, which allows tracing changes in the economic life of both the capital of the Russian Empire and some of its inhabitants (German bakers). The devastating wars in Central and Eastern Europe provoked labor migration, as a result of which many Germans moved to Russia in the 18th century. One of the economic “niches” that they successfully occupied in the capital was the production of bread. In this domain, migrants-Germans formed the majority at the turn of the 18th and 19th centuries. Later, the natives of Saint-Petersburg prevailed among German bakers. In the 1820s and 1840s, they managed to monopolize the city's grain market, holding the leadership until the 1880s. During the post-reform period, under the conditions of the interethnic division of labor, they were pushed by numerous Jewish burghers who got engaged into breadmaking. In order to maintain their positions, German craftsmen started modernization of their workshops. As a result of technical transformations, electric motors and various mechanical devices became widespread, which contributed to the transformation of the technological cycle. However, these changes did not lead to a massive intensification in production.